The Impact of Social Media on Academic Performance of Students in Nigerian Colleges: Case Study of Adamawa State College of Education Hong, Nigeria - Mathias, Linus; Hickson, Sikari; Jarison, Giliki; Jonathan, Nelson (Kwaghe International Journal of Engineering and Information Technology, 2026)
Social media usage is increasing as human society shifts online, facilitating global connections and offering time and cost savings. It enhances student satisfaction and academic performance by influencing technical, task, and social aspects. Utilizing social media for educational purposes can improve comprehension, but its addictive nature may lead to distractions if not managed well. The study involved 2,340 students from Adamawa State College of Education, Hong, randomly selected, with a sample size derived from a confidence interval of 5 and a 95% confidence level. Student data were collected via a questionnaire, which included options for responses ranging from Strongly Agree to Strongly Disagree. Out of 1,500 distributed questionnaires, results showed a diverse demographic: 719 were in NCE III (30.7%), 762 in NCE II (32.6%), and the remainder in NCE I. Gender-wise, 1,014 students were male (43.3%) and 1,326 female (56.7%). The majority age group was 21–25, comprising 1,305 students, while ages 16–20 accounted for 912 students. Regular social media use was reported by 11.7% of students, yet 88.3% logged in daily, suggesting potential impacts on academic performance. Facebook and WhatsApp emerged as the most utilized platforms, favored for their convenience, while some students also engaged with Instagram and YouTube for collaborative study and social communication. However, non-academic use of social media could negatively influence academic results.